2020
DOI: 10.21475/ajcs.20.14.03.p1997
|View full text |Cite
|
Sign up to set email alerts
|

Biocidal potential of some organic by-products on sanitary and physiological quality of red and white fava beans seeds

Abstract: Fava bean (Phaseolus lunatus L.), is a rustic species and has great adaptability to arid regions of Brazil and stands out for its social importance and high levels of protein. Even so, the culture presents low productivity due to several factors, such as the quality of the seed. In this sense, the objective of this study was to evaluate the fungitoxic action of organic products, namely vinasse, cassava wastewater and agave extract, isolated and mixed, for treatment of beans seeds. The experimental design was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Fusarium verticillioides is known as one of the main pathogens of maize plants, reducing grain productivity worldwide (Leslie & Summerell, 2006;Watson, Burgess, Summerell & O'keeffe, 2014). Mota et al (2017) and Sousa et al (2020) reported that F. verticillioides infects fava beans in Brazil, however, the diagnosis was made based only on morphological characteristics. Thus, this paper comprises the first record of F. verticillioides in fava beans in Brazil, based on phylogenetic analyzes.…”
Section: Results E Discussionmentioning
confidence: 99%
“…Fusarium verticillioides is known as one of the main pathogens of maize plants, reducing grain productivity worldwide (Leslie & Summerell, 2006;Watson, Burgess, Summerell & O'keeffe, 2014). Mota et al (2017) and Sousa et al (2020) reported that F. verticillioides infects fava beans in Brazil, however, the diagnosis was made based only on morphological characteristics. Thus, this paper comprises the first record of F. verticillioides in fava beans in Brazil, based on phylogenetic analyzes.…”
Section: Results E Discussionmentioning
confidence: 99%
“…Several studies have emphasized the efficiency of vinasse on pathogens by facilitating the decomposition of organic matter, thereby releasing volatile fatty acids that exhibit detrimental effects on both fungi and nematodes [19,41]. At the same time, vinasse serves as a nutritional source for the multiplication of antagonistic microorganisms, which indirectly enhances the control of plant pathogens [42,43]. However, there is little information that explains the direct action of vinasse on phytonematodes.…”
Section: Discussionmentioning
confidence: 99%